Peningkatan kapasitas keluarga pekerja migran melalui pola pengasuhan berbasis komunitas di desa Borok Toyang - Yani, Ahmad; Kholissusa’di, M.; Hardiansyah, Rila; Herlina, Herlina; Wahyuni, Tri (Universitas Hamzanwadi, 2024)
Borok Toyang Village, as one of the regions with a high number of female migrant workers, faces significant challenges in parenting due to parental migration. This study aims to enhance the capacity of migrant worker families through community-based parenting practices. The activity involved 30 participants, including parents, substitute families, and other community members. Methods included workshops, information services, direct discussions, and case studies. The results showed that the participants' average understanding scores increased from 45 to 80, with 85% of participants reporting improved understanding and 70% feeling more confident in implementing parenting strategies. Key challenges identified included limited knowledge of children's emotional needs and reliance on substitute caregivers. This community-based approach proved effective in enhancing the understanding and skills of migrant worker families, involving village authorities and the community as key supporters. This program provides a strong foundation for replication in other communities facing similar conditions